Regulation of defensive function on gingival epithelial cells can prevent periodontal disease - Fujita, Tsuyoshi (Jpn Dent Sci Rev, 2018)
Periodontal disease is a bacterial biofilm-associated inflammatory disease that has been implicated in many systemic diseases. A new preventive method for periodontal disease needs to be developed in order to promote the health of the elderly in a super-aged society. The gingival epithelium plays an important role as a mechanical barrier against bacterial invasion and a part of the innate immune response to infectious inflammation in periodontal tissue. The disorganization of cell–cell interactions and subsequent inflammation contribute to the initiation of periodontal disease. These make us consider that regulation of host defensive functions, epithelial barrier and neutrophil activity, may become novel preventive methods for periodontal inflammation. Based on this concept, we have found that several agents regulate the barrier function of gingival epithelial cells and suppress the accumulation of neutrophils in the gingival epithelium. We herein introduce the actions of irsogladine maleate, azithromycin, amphotericin B, and Houttuynia cordata (dokudami in Japanese), which is commonly used in traditional medicine, on the epithelial barrier and neutrophil migration in gingival epithelial cells in vivo and in vitro, in order to provide support for the clinical application of these agents to the prevention of periodontal inflammation.